Managerial Ownership and Agency Cost: Evidence from Bangladesh - Rashid, Afzalur (Journal of business ethics, 2016)
This study examines the influence of managerial ownership on firm agency costs among listed firms in Bangladesh. This is an institutional setting that features a mixture of agency costs. This institutional setting has a concentration of ownership by managers, but the firms are not solely owned by managers. The extant literature suggests that the sacrifice of wealth by the principal and potential costs associated with monitoring the agents is known as the agency cost. This study uses three measures of agency cost: the ‘expense ratio’, the ‘Q-free cash flow interaction’, and the ‘asset utilisation ratio’. The finding of the study is that managerial ownership reduces the firm agency cost only under the ‘asset utilisation ratio’ measure of agency cost; this is robust with regard to a number of robustness tests. Furthermore, the non-linearity tests suggest that the convergence of interest is evident with very high and low levels of managerial ownership. The entrenchment effect by the owners is evident at moderate levels of managerial ownership. Although there has been great scepticism among management researchers on the validity of agency theory, overall, the findings of this study do not reject the validity of agency theory. Given that the entrenchment by managers is evident at certain levels of ownership and that the agency problem may still exist between insiders and outsiders, legislative guidelines for controlling share ownership may be required.